Lived Experiences of Newly Hired Teachers: Basis for Policy Recommendations - Ponciana Quimque (Philippine Association of Institutions for Research, Inc., 2020)
This phenomenological study described the lived experiences of newly hired teachers about their journey towards achieving the goal of imparting knowledge among their students and attaining excellence in their chosen profession. The testimonies of the participants provided bases for policy recommendations. The study was participated by ten (10) teachers who were purposively and randomly sampled among public elementary schools in the Schools Division of Calamba City. The purpose was to obtain participants from the rostrum of teachers with a 5-year length of service. An interview guide question was used during the Focus Group Discussion (FGD). The following themes emerged from the experiences shared by the participants: unprepared, under pressure, high expectations, opportunity, errands, culture shock, accountability, confusion, tradition, challenging, and unequipped. These and all other challenges in classroom management and instructions, students' behavior and varied abilities, and lack of resources changed the life of newly hired teachers. They coped with all these challenges by doing researches, being updated, asked for technical assistance, and pursuing continuing professional development. Policy recommendations on deployment and handling of newly hired teachers were highlighted: Process of Assigning Tasks among Newly Hired Teachers, Classroom Management and Discipline, and Diversity of Learners, Interruption of Teaching-Learning Process, and Having a Good Start.